(untitled) (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Spinal anesthesia is a safe and acceptable technique for patients undergoing caesarean section because it provides both excellent analgesia and muscle relaxation. Post Dural Puncture Headache (PDPH) is frequently reported complication after spinal anesthesia. This study evaluates the incidence of PDPH following early mobilization and recumbency after caesarean section. Methods: This prospective, randomized comparative interventional study included 100 parturients women of age 18 to 45 years, ASA I and II, randomly divided into two groups – Ambulatory ‘A’ and Recumbent ‘R’. At the end of caesarean section, patients were advised to either lie in recumbent position for 24 hours or mobilize as soon as they become ambulatory after spinal aneshthesia. Occurrence of headache were recorded at 24 hours, 72 hours and 7th day. Software SPSS 16, chi-square test was used for proportions like incidence and severity of PDPH; p<0.05 was taken as significant. Results: The incidence of PDPH was statistically not different (p = 0.361) in Group R 8% (4 patients) and in Group A 6% (3 patients). In both the groups, the severity of headache was mild to moderate with only mild headaches in the Group A (p = 0.549). Conclusions: Early ambulation following spinal anesthesia for caesarean section did not increase the incidence of PDPH in parturients.